Estudo de vidros fosfatos dopados com terras raras para aplicação em fibras ópticas e guias de ondas planares - Santos, Jaime Vitalino (2006)
In this work, the thermal and optical properties is of the system P2O5 - ZnO - Al2O3 - AO - PbO - La2O3 (mol %) + XEr2O3 [A = Ba; Mg; X = 0; 1; 2; 3; 4; 5 (wt %)] was studied aiming at applications in optical fibres and planar waves-guides, as optical amplifiers. Such system is unknown and of low cost if compared with others, for example, those made with tellurium oxide, aiming production in the industrial scale. This research was developed in three consecutive stages, where in the first one the concentration of La2O3 was varied considering to get systems with reasonable thermal stability and optical properties. In the second stage, chosen the best composition with fixed La2O3 (mol%), looking for change the concentration of PbO and verify the change in the refractive index. Already in the third and last stage one searched to elaborate a glass from increasing concentrations of Er2O3 (wt %) aiming an optical amplification around 1530 nm. Therefore, ahead of the general objective of this research, it is of basic importance to study thermal and optical properties, such as transmittance, refractive index and differential scanning calorimetry, of the glasses resultants in each of these three stages. It was observed, in the first stage, that this system presents greater glass stability (GS - glass stability) and reasonable optical properties, when the composition contains 10La2O3 (mol %). Already in the second stage, keeping fixed 10La2O3 (mol %), this system presents greater index of refraction, when in its composition contains 10PbO (mol %) and A = Ba. Finally, in the third stage, it was observed that the biggest value of life time of the state 4I13/2 of Er3+ is 1,2 ms, for a 1Er2O3 (wt%) concentration. Ahead of this value of the life time and the thermal and optical properties, observed in all the three stages, one concludes that considered unknown systems in this research, with its compositions, suggested for the construction of the cladding and the core of a possible optical fibre are 63P2O5 . 14ZnO . 1Al2O3 . 10MgO. 2PbO. 10La2O3 (mol%) and 55P2O5. 14ZnO. 1Al2O3 . 10BaO. 10PbO. 10La2O3 (mol%) + 1Er2O3 (wt%), exactly not being these concentrations that had presented greater width of the half height of the emission band of the transition 4I13/2 → 4I15/2.